Underreporting of the tuberculosis and AIDS comorbidity: an application of the linkage method - Carvalho, Carolina Novaes; Dourado, Ines; Bierrenbach, Ana Luiza (Revista de Saúde Pública, 2011)
OBJECTIVE: To analyze the underreporting of the tuberculosis (TB) and AIDS comorbidity. METHODS: Surveillance study using records from the Notifiable Diseases Information System - Tuberculosis and AIDS in Brazil from 2000 to 2005. Records of TB without information on the presence of Aids were considered to be underreporting of the comorbidity when paired off with AIDS records in which the year of diagnosis of AIDS was the same or previous to the year of reporting of TB, as well as records from the same patient whose previous records had this information. An indicator was created: recognized TB-AIDS comorbidity, based on the TB records that had information on the presence of AIDS. RESULTS: The underreporting of TB-AIDS was 17.7%. This percentage varied between states. The incorporation of the underreported records into the previously recognized ones increased the proportion of TB-AIDS in Brazil from 6.9% to 8.4%. The highest proportions of underreporting were noted in Acre (Northern), Alagoas, Maranhão and Piauí (Northeastern) (more than 35% each) and the lowest in São Paulo (Southeastern) and Goiás (Central-western) (around 10% each). CONCLUSIONS: The underreporting of the TB-AIDS comorbidity found in Brazil will probably trigger modifications in the surveillance system in order to provide information for the national programs.